Designing timber connections for ductility – A review and discussion. (18th October 2021) - Ottenhaus, Lisa-Mareike; Jockwer, Robert; van Drimmelen, David; Crews, Keith
Highlights: The importance of ductile connection design was highlighted. Common challenges in ductile connection design were addressed. Best-practice connection design approaches were reviewed. Simple performance-based design criteria to ensure connection ductility were suggested. Abstract: This paper discusses the design principles of timber connections for ductility with focus on laterally-loaded dowel-type fasteners. Timber connections are critical components of timber structures: not only do they join members, but they also affect load capacity, stiffness, and ductility of the overall system. Moreover, due to the brittle failure behaviour of timber when loaded in tension or shear, they are often the only source of ductility and energy dissipation in the structure in case of overloading, much like a fuse in an electrical circuit. This paper addresses current challenges in connection design for ductility, reviews selected best-practice design approaches to ensure ductility in timber connections, suggests simple performance-based design criteria to design connections for ductility, and aims to stimulate a discussion around potential solutions to implement safe design principles for ductile connections in future design codes and connection testing regimes.